The Degree of Availability of Reading ‎Comprehension Strategies among Female ‎Arabic Language Teachers in Teaching ‎Reading for Grades (5-10) Female Students in ‎the Sultanate of Oman ‎ - Al-Housniah, Afraa (Jordan Journal of Educational Sciences, 2021)
This study aimed to identify reading comprehension strategies that should be available among female Arabic language teachers in teaching reading for grades (5-10) female students find the availability degree of these strategies among female Arabic teachers in teaching reading. To achieve both goals, the researcher prepared a list of reading comprehension strategies and after verifying its truthfulness and consistency, the researcher included it into a note card that includes (5) main strategies: (predicting, connecting, self–questioning, mental perception and summarizing). Each one includes several sub-strategies with the total of (19) strategies. She applied this card to a random sample of (36) female Arabic teachers from schools in the Directorate of Education, North Batinah Governorate, for grades (5-10) in the Sultnate of Oman. The findings revealed that the degree of availability of reading comprehension strategies among female Arabic language teachers in teaching reading for grades (5-10) female students was average for all strategies, except for the self-questioning strategy, for which the availability degree was low